DEVELOPING MARKETING STRATEGY OF MADANA TILES SURABAYA TO ENTER THE NEW MARKET ON SOUTHEAST ASIA - Evania Liana Marcos; Reynold Richardo (AIBPM Publisher, 2018)
Madana Tiles is the first cement tile company in Surabaya city. Due to being produced entirely by hand, the Tile of Madana Tiles is assured of its authenticity and uniqueness. With a periodically supervised production process, it allows us to control the entire process with the best results and competitive pricing.Cement tiles have been used and produced in Indonesia for tens or even hundreds of years, and have become part of Indonesian culture, therefore, the vision of madana tile is to preserve the culture by introducing its products and providing opportunities to the community by opening employment. Of course we also want to work with architects, interior designers, and customers as much as possible so as to enable the creation of innovations in design. Customers can also design their own tile design. Madana Tiles already has a web, but the web is not yet complete including catalogs. The incomplete Web can make consumers unable to guess what kind of tiles Madana Tiles produces. We from team 21 have some ideas that can help marketing tiles Madana Tiles is by using the catalog as a means of promotion. We will make the catalog in the form of e-catalog (2D) and real catalog (3D). Why do we recommend Madana Tiles to create an e-catalog, because on the web Madana Tiles belom has a complete catalog so that consumers who see the web can not choose the tile design variations. As for the 3D catalog, consumers can see directly the variations, designs and colors of the finished tiles. Our team chose the Southeast Asia sector because there are several opportunities. Cambodia, Laos, Malaysia, Singapore, Thailand. Among its centralized locations, the country wants to expand its trade and investment activities, has abundant natural resources and has advanced technology and economics.